Evaluation of estrogenic, antiestrogenic and genotoxic activity of nemorosone, the major compound found in brown Cuban propolis - Camargo, Mariana S. [UNESP] (2013)
Background: Brown propolis is the major type of propolis found in Cuba; its principal component is nemorosone, the major constituent of Clusia rosea floral resins. Nemorosone has received increasing attention due to its strong in vitro anti-cancer action. The citotoxicity of nemorosone in several human cancer cell lines has been reported and correlated to the direct action it has on the estrogen receptor (ER). Breast cancer can be treated with agents that target estrogen-mediated signaling, such as antiestrogens. Phytoestrogen can mimic or modulate the actions of endogenous estrogens and the treatment of breast cancer with phytoestrogens may be a valid strategy, since they have shown anti-cancer activity.Methods: The aim of the present investigation was to assess the capacity of nemorosone to interact with ERs, by Recombinant Yeast Assay (RYA) and E-screen assays, and to determine by comet assay, if the compound causes DNA-damaging in tumoral and non-tumoral breast cells.Results: Nemorosone did not present estrogenic activity, however, it inhibited the 17-β-estradiol (E2) action when either of both methods was used, showing their antiestrogenicity. The DNA damage induced by the benzophenone in cancer and normal breast cells presented negative results.Conclusion: These findings suggest that nemorosone may have therapeutic application in the treatment of breast cancer. © 2013 Camargo et al.; licensee BioMed Central Ltd.